Valorization of cockle shell waste into hydroxyapatite for improving gel properties of surimi - Hasan, Mohamad Rais; Che Abdullah, Che Azurahanim; Mustapha, Nor Afizah; Mohd Ghazali, Mohd Sabri; Noranizan, Mohd Adzahan (John Wiley and Sons, 2025)
Modern surimi production uses leftover fish, supporting sustainable utilization of fishery resource. However, the use of commercial additives to enhance gel quality increases production costs. Exploring alternative, low-cost functional ingredients like hydroxyapatite (HAp) from seafood shells is still limited. This study examines the impact of cockle shell-derived HAp on the gelling properties of surimi. Surimi gels were formulated with different HAp concentrations (0.1, 0.5, 1.0, and 1.5%) and compared to a control without HAp. Key parameters analyzed include WHC, EMC, CLR, rheological behavior, texture, microstructure, chemical composition, and thermal stability. HAp supplementation showed no significant effect on water retention properties. At 0.1%, HAp increased the storage modulus (G′), enhancing the gel's solid-like characteristics. HAp addition at this concentration led to higher gel hardness and better texture attributes. The microstructure revealed a denser gel network with small, well-connected pores at 0.1% HAp. Uniform Ca and P distribution indicated even dispersion of HAp within the gel matrix. HAp at 0.1% also reduced gelation temperature, indicating improved gelation efficiency. Overall, cockle shell-derived HAp at low concentration improved surimi gel quality effectively. This suggests its potential as a sustainable ingredient in surimi processing. Practical Applications: This study shows that adding a small amount (0.1%) of hydroxyapatite from cockle shells can improve the texture and gel strength of surimi products. This natural, seafood-based additive offers a cost-effective and sustainable alternative to commercial binders in fish paste products for food manufacturers.